مجلة دراسات في التاريخ والاثار 71: العالم والمحدث والامام الـعابد عبد الله بن المبارك المتوفى( سنة 181 هــ - 797 م ) - عمران وفاء عبد الجبار (مجلة دراسات في التاريخ والآثار, 2020)
الملخص Conclusion Khurassan and Marrow are considered the most famous Islamic cities for their scholars and sciences and they both became a passage for the other countries around the world .Thus, Abdullah bin Al-Mubarek was one of those scholars who was characterized by his social ,ethical, scientific, and cultural traits in his life. Such an apathetic scholar and a generous man had suffered much in his life’s stages from childhood till old age ,but he kept on struggling till he managed to become an educated person . Abdullah bin Al-Mubarek was one of the modernizers who was a remarkable figure in Prophetic Tradition as admitted by other scholars and jurists .Such status reached by this scholar resulted from instructing from other sheiks , and later on had his own countless number of students to the degree that he was highly praised by famous poets in his time .